The Concept of Justice in the Quran Perspective: A Social Critique of Orphans' Wealth Management in Surah Al-An'am Verse 152 - Muhajiroh, Hanifah; Dahliana, Yeti (Universitas Muhammadiyah Surakarta, 2024)
The concept of justice in the perspective of the quran: a fundamental principle in establishing a harmonious and sustainable social order One of the aspects of justice that receives significant attention in Islam is the protection of orphans' rights. Surah Al-An’am verse 152 emphasizes the importance of managing orphans' wealth fairly and responsibly. This verse asserts that their assets must not be misused and should only be utilized for beneficial purposes until they reach maturity. This study employs a qualitative research method and adopts a library research approach, conducting a critical and in-depth analysis of relevant literature, including books and scholarly journals. The research aims to explore the Quranic perspective on justice in managing orphans' wealth while critically examining social practices in Arab societies that often contradict the principles of justice. By referencing classical and contemporary interpretations, this study seeks to provide a deeper understanding of justice in managing orphans' wealth and its implications for the Islamic social system. Social criticism of practices that deviate from Islamic justice values is expected to serve as a reflection for society in maintaining the trust of orphaned assets and upholding justice in everyday life.